Using Digital Game Wordwall in Supporting English Vocabulary Mastery - Rattri, Artha Rattri Wardhana; Rachman, Dzul (Borneo Educational Journal (Borju), 2024)
English, a global language, weaves through education, business, relationships, technology, and science. Mastering vocabulary is pivotal for English proficiency. Utilizing media for vocabulary learning engages and challenges students, rendering the process more enjoyable and effective. This study looks into the effectiveness of using the digital game Wordwall to assist English Vocabulary Mastery at SMP Negeri 8 Samarinda. This study is being undertaken with the eighth graders of SMP Negeri 8 Samarinda. In this study, the researcher uses a mixed method with quasi-experimental design to compare two classes. The focus of this research is eighth grade, namely VIII C and VIII D. VIII D is the experimental class with 21 students and VIII C is the control class with 27 students. The quantitative data is acquired using multiple choice and fill-in-the-blank tests. Qualitative data is gathered through interviews. The results suggest that Wordwall media is effective in improving the vocabulary. Furthermore, Wordwall is a game/application that adds excitement, enthusiasm, and enjoyment to the learning environment. Wordwall entices students to use the application because to its appealing interface, simple gameplay, and broad selection of games.